SURVEY ON AWARENESS OF TREATMENT PLANNING IN TEMPOROMANDIBULAR DISORDER AMONG DENTISTS - Prakash, Satya; Ganapathy, Dhanraj; V, Ashok (International Journal of Psychosocial Rehabilitation, 2020)
A temporomandibular disorder (TMD) is a musculoskeletal disorder within the masticatory system. Many practitioners refer to TMD as a single disorder in spite of the fact that patients have various sub-diagnoses such as, myofascial pain, temporomandibular joint (TMJ) inflammation. TMD is a prevalent disorder most commonly observed in individuals between the ages of 20 and 40. AIM: To evaluate the awareness of various treatment planning in temporomandibular disorder among dentists. MATERIALS AND METHODS: A cross-sectional study was done among general dentists. Sample size of 100 was chosen. Self-administered questionnaire containing 6 open questions were distributed. The data obtained were then analyzed. RESULTS: 64.2% of the dental practitioners know how to manage a patient with temporomandibular joint disorder but they are not sure of the outcome.20% of the dental practitioner use RDC criteria for the evaluation of the temporomandibular joint .69.8% of dental practitioners believe soft splint is the most effective occlusal splint therapy available for the treatment of TMD. CONCLUSION: The awareness of various treatment planning in temporomandibular disorder among dentists is adequate. More awareness on temporomandibular disorder should be created by conducting workshops and Continuing Dental Education programs.